Analisis Kemampuan Berpikir Kritis dalam Pembelajaran IPA Materi dan Sifatnya Siswa Kelas V SDN Kebon Dalem - Septiani, Trimia; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The ability to think critically needs to be possessed by students, so that students are able to think and understand the material and basic concepts they are learning and can solve the problems they face by providing explanations in the form of appropriate conclusions in their own language. Researchers conducted research on critical thinking skills in learning natural science material objects and their nature in fifth grade elementary school students. The subjects of this study were the fifth grade students of SDN Kebon Dalem as many as 14 students. This study uses a qualitative approach with a qualitative descriptive method. The research instruments taken were tests, interviews and written documents in the form of critical thinking ability test results. This study aims to describe the ability to think critically in learning the material science of objects and their nature in the fifth grade students of SDN Kebon Dalem. The findings of the study indicate that the critical thinking ability of fifth grade students in science learning material objects and their nature is that the average class is included in the critical enough criteria of 65.2%. Meanwhile, the indicator of critical thinking ability that is strong and able to be answered correctly and thoroughly by students is the indicator of being able to ask questions by 85.7%, while the weakest indicator is the indicator of being able to analyze arguments by 52.3%.